Illness Uncertainty in Parents of Children with Juvenile Idiopathic Arthritis - Pearce, Caroline (ACR Open Rheumatol, 2021)
OBJECTIVE: To gain a better understanding of uncertainty regarding the illness experienced by parents of children with juvenile idiopathic arthritis (JIA). METHODS: Parents/guardians of a child or young person (aged less than 18 years) diagnosed JIA were recruited in the United Kingdom via the National Rheumatoid Arthritis Society JIA group. Semistructured telephone interviews were conducted with the parents. RESULTS: Twenty parents took part, including 19 mothers and one father. Their children with JIA were mostly female (n = 15; 75%) with polyarticular arthritis (n = 12; 60%), averaged 8 years of age, and had been diagnosed for a mean of 3.7 (SD 2.3) years. Parents expressed uncertainty in the following five key domains: diagnosis, cause, symptoms, and prognosis; medical management; impact; parenting uncertainty; and awareness of JIA. All participants expressed uncertainty in at least four of the five domains. Although parents’ uncertainty in the early stages of the disease related to lack of information and understanding of JIA, much uncertainty could not be resolved by receipt of information. These included concerns about their child’s future and a lack of support with managing the emotional aspects of living with JIA. CONCLUSION: We found that parents’ experiences of uncertainty went beyond dealing with the purely medical aspects of JIA. Provision of information about JIA, although essential, is not sufficient to help parents manage the considerable uncertainty they experience about many aspects of their child’s JIA. Identifying ways to incorporate support for coping with uncertainty into routine care will be an important way of supporting parents to care for their child with JIA.